Answer:
See explanation
Step-by-step explanation:
1 = b (0,-2)
2 = b (0,1)
6 = a (3,0)
7 = a (-2,2)
Answer:
0
Step-by-step explanation:
Slope is calculated y2-y1/x2-x1
18-18/0-3
0/-3
0
The slope of the line that passes through the following points is undefined
<em><u>Solution:</u></em>
Given that, We have to find the slope of line passing through two points
Given points are (-1, 5) and (-1, 6)
<em><u>The slope of line is given by formula:</u></em>
![m = \frac{y_2-y_1}{x_2-x_1}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7By_2-y_1%7D%7Bx_2-x_1%7D)
From given,
![(x_1, y_1) = (-1, 5)\\\\(x_2, y_2) = (-1, 6)](https://tex.z-dn.net/?f=%28x_1%2C%20y_1%29%20%3D%20%28-1%2C%205%29%5C%5C%5C%5C%28x_2%2C%20y_2%29%20%3D%20%28-1%2C%206%29)
<em><u>Substituting the values we get,</u></em>
![m = \frac{6-5}{-1-(-1)}\\\\m = \frac{1}{-1+1}\\\\m = \frac{1}{0}](https://tex.z-dn.net/?f=m%20%3D%20%5Cfrac%7B6-5%7D%7B-1-%28-1%29%7D%5C%5C%5C%5Cm%20%3D%20%5Cfrac%7B1%7D%7B-1%2B1%7D%5C%5C%5C%5Cm%20%3D%20%5Cfrac%7B1%7D%7B0%7D)
Thus the slope is undefined
Answer:;4.4
Step-by-step explanation: Since it varies inversely we know G times H squared is equal to some constant, k. So we have G*H*H=k. We are told that when H=4, G=.25. Plugging this in, we have .25*4*4=k. This simplifies to 4=k. Our new equation is G*H*H=4. Now, we want to solve for G when H=.3. We plug it in. G*.3*.3=4 => G*.09=4. G=4/.09. This means G is approximately 44.4.
Ashes2049, are you good at geometry?